Computing Location from Ambient FM Radio Signals - Youssef, Adel; Krumm, John; Miller, Ed; Cermak, Gerry; Horvitz, Eric (Wireless Communications and Networking Conference, 2005 IEEE, 2004)
We present a method for computing the location of a device down to a radius of several miles within a greater metropolitan area by analyzing the signal strengths observed from commercial FM radio stations. The use of ambient commercial radio signals allows for wide coverage, both indoor and outdoor reception, client-side computing for privacy, and the feasibility of employing inexpensive, low-power measurement hardware. Our technique is based on a model for computing the likelihood of locations using both received signal strengths and information from a simulated signal strength map. Using simulated signal strengths relieves the burden of manually measuring signal strength as a function of location. We account for the inevitable measurement variations among devices by comparing rankings of radio stations by signal strength. Our experiments show we can measure location down to a median error of about 8 kilometers (5 miles) in the greater Seattle area by listening to seven different radio stations.